TrkA, But Not TrkC, Receptors Are Essential for Survival of Sympathetic Neurons In Vivo - Fagan, Anne M. (J Neurosci, 1996)
Neurotrophins and their signaling receptors, the Trk family of protein tyrosine kinases, play a major role in the development of the mammalian nervous system. To determine the precise stages that require Trk receptor signaling during development of the sympathetic system, we have analyzed the superior cervical ganglion (SCG) of embryonic and postnatal mice defective for each of the known Trk receptors. Transcripts encoding TrkC are detected in early sympathetic development, before the coalescence of the SCG. trkA expression appears at E13.5, becoming robust from E15.5 onward. In contrast, trkC expression decreases significantly after E15.5 and remains detectable only in a small subpopulation of cells. No significant trkB expression could be detected in the SCG at any developmental stage. Ablation of TrkA receptors does not affect neurogenesis, expression of neuronal markers, or initial axonal growth. However, these receptors are absolutely necessary for the survival of sympathetic neurons after E15.5 and for proper innervation of their distal targets. In contrast, mice defective for either TrkC or TrkB tyrosine kinase receptors do not display detectable defects in their SCGs. These results illustrate the differential roles of the Trk family of receptors during SCG development and define a critical role for TrkA signaling in the survival, but not differentiation, of SCG neurons. Moreover, these observations raise the possibility that at least some SCG neurons become neurotrophin-dependent before complete target innervation.